Enantioseparation of tartaric acid by ligand-exchange capillary electrophoresis using contactless conductivity detection - Knob, Radim; Petr, Jan; Sevčík, Juraj; Maier, Vítězslav (Journal of separation science, 2013)
A method for the determination of tartaric acid enantiomers using CE with contactless conductivity detection has been developed. Cu(II) as a central metal ion together with L-hydroxyproline were used as a chiral selector, the BGE was composed of 7 mM CuCl2, 14 mM trans-4-hydroxy-L-proline, and 100 mM ε-aminocaproic acid; the pH was adjusted to 5 by hydrochloric acid. Separation with a resolution of 1.9 was achieved in 9 min in a polyacrylamide-coated capillary to suppress the EOF. Various counterions of the BGE were studied, and migration order reversal was achieved when switching from ε-aminocaproic acid to L-histidine. With detection limits of about 20 μM, the method was applied to the analysis of wine and grape samples; only L-tartaric acid was found.
Keywords: Vitis; Wine; rostlinné extrakty; tartaráty; Tartrates; Stereoisomerism; elektroforéza kapilární; víno; Electrophoresis, Capillary; Plant Extracts; stereoizomerie